Canadian Consensus-based and Evidence-based Guidelines for Benign Endometrial Pathology Reporting in Biopsy Material. (March 2019) - Parra-Herran, Carlos; Cesari, Matthew; Djordjevic, Bojana; Grondin, Katherine; Kinloch, Mary; Köbel, Martin; Pirzada, Amrah; Plotkin, Anna; Gilks, C. Blake
Abstract : Standardized terminology has proven benefits in cancer reporting; in contrast, reporting of benign diagnoses in endometrial biopsy currently lacks such standardization. Unification and update on the lexicon can provide the structure and consistency needed for optimal patient care and quality assurance purposes. The Special Interest Group in Gynecologic Pathology of the Canadian Association of Pathologists-Association Canadienne des Pathologistes (CAP-ACP) embarked in an initiative to address the current need for consensus terminology in benign endometrial biopsy pathology reporting. Nine members of the Special Interest Group developed a guideline for structured diagnosis of benign endometrial pathology through critical appraisal of the available peer-reviewed literature and joint discussions. The first version of the document was circulated for feedback to a group of professionals in akin fields, the CAP-ACP Executive Committee and the CAP-ACP general membership. The final 1-page document included 17 diagnostic terms comprising the most common benign endometrial entities, as well as explanatory notes for pathologists. The proposed terminology was implemented in the practice of 5 pathologists from the group, who applied the guideline to all benign endometrial biopsies over a 2-wk period. A total of 212 benign endometrial biopsies were evaluated in this implementation step; the recommended terminology adequately covered the diagnosis in 203 cases (95.8%). A list of terminology for benign endometrial biopsy reporting, based on expert consensus and critical appraisal of the available literature, is presented. On the basis of our results of implementation at multiple centers, the proposed guideline can successfully cover the large majority of diagnostic scenarios. The document has the potential to positively impact patient care, promote quality assurance, and facilitate research initiatives aimed at improving histopathologic assessment of benign endometrium.